Assessment of Systemic Lupus Erythematosus in Term of Serum Anti-nucleosome and Interleukin 12 Markers in Relation to Epstein–Barr virus and Cytomegalovirus - Saif S. Ibrahem1 , Ahmed Sahib Abdulamir2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease, more dominant in female, associated with high risk of life threating complication and increase morbidity and mortality. the exact cause of SLE is not yet known with many suggestions about a possible role of viral infection in the development of the disease. Epstein –Barr virus is the most commonly studied virus in an attempt to prove its presumed association with development of SLE.The objectives of this study are the measurement of the effect of CMV and EBV seropositivity in the auto immune status and severity of disease SLE measured by estimating the level of immunological markers anti-nucleosome and IL-12 with viral marker. Materials and Method: Forty newly diagnosed female with SLE were randomly selected from patient attended rheumatology clinic at medical city in Baghdad during the period between December 2018 to May In addition, with 40 apparently healthy females, as, a control groups. Both group were investigated for IL12, anti-nucleosome, EA, VCA, EBNA and CMV by ELISA and the results were statistically evaluated. Results: The studied viral markers in the current study which included EBV markers EA, VCA, EBNA, have shown significantly higher level compared to the control group. Similarly, anti-nucleosome and IL12 have shown significantly higher level compared to the control group. Conclusions: The possible defect in controlling viral infection and increased number of latent infected cell in SLE may enhance production of auto-antibodies